2021
DOI: 10.1371/journal.pone.0246026
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Indian Ocean Lineage Chikungunya virus RNA in field collected Culex quinquefasciatus Say from Bangkok, Thailand but no evidence of virus replication

Abstract: Following an outbreak of chikungunya virus (CHIKV) infections in Thailand in 2019, numerous cases of CHIKV infection have been diagnosed in Bangkok, the capital of the country. In our previous investigation of the vectors for disease transmission, we found natural infection of CHIKV in both male and female Aedes aegypti mosquitoes collected from the outbreak areas in Bangkok. Some reports mentioned the detection of CHIKV in Culex mosquitoes. In Thailand, the Culex quinquefasciatus Say mosquito is a common spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Likewise, a vector competence study comparing Italy 2007 and Italy 2017 strains in Aedes albopictus, the localized vector in Italy, showed that both had similar infection and transmission rates [49]. In addition, in the large-scale outbreak of IOL sub-lineage E1-K211E/E2-V264A carrying E1-I317V in Thailand during 2018-2020, Aedes aegypti was identified as the primary vector, and viral RNA was also found in another mosquito species, Culex quinquefasciatus [50,51]. In Mombasa, Kenya, these two mosquito species might have played a role in the outbreak of IOL sub-lineage E1-K211E/E2-V264A/E1-I317V [41,52].…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, a vector competence study comparing Italy 2007 and Italy 2017 strains in Aedes albopictus, the localized vector in Italy, showed that both had similar infection and transmission rates [49]. In addition, in the large-scale outbreak of IOL sub-lineage E1-K211E/E2-V264A carrying E1-I317V in Thailand during 2018-2020, Aedes aegypti was identified as the primary vector, and viral RNA was also found in another mosquito species, Culex quinquefasciatus [50,51]. In Mombasa, Kenya, these two mosquito species might have played a role in the outbreak of IOL sub-lineage E1-K211E/E2-V264A/E1-I317V [41,52].…”
Section: Discussionmentioning
confidence: 98%